IGSF3-mediated potassium dysregulation promotes neuronal hyperexcitability and glioma progression - Venkataramani, Varun (Trends in cancer, 2023)
Glioblastomas are incurable tumors often associated with epileptic seizures. In a recent study published in Neuron, Curry et al. demonstrated a novel function of the membrane protein IGSF3 that induces potassium dysregulation, neuronal hyperexcitability, and tumor progression. This work uncovers a novel layer of bidirectional neuron-tumor communication, further underlining the importance of comprehensively investigating neuron-tumor networks in glioblastoma.
Online verfügbar: 24. April 2023, Artikelversion: 16. Mai 2023
Gesehen am 02.10.2023